A rare complication of tuberculosis: chronic empyema thoracis with bronchopleural fistula - a case report - Masood, Shaik Ontela; Supriya, Guntennagari; Aswini, Ubbara; Soheb, Shaik Muhammad; Reddy, Vemareddy Ahindra; Rafi, Minnalagaari Muhammad; Gurukul, Tharun Vinay (International Journal of Research in Medical Sciences, 2025)
Bronchopleural fistula associated with chronic empyema thoracis is an uncommon and potentially fatal tuberculosis (TB) complication. Bronchopleural fistula remains one of the most serious life-threatening complications but is fortunately rare. We report a case of a 24-year-old male who presented with cough with expectoration, breathing difficulty, pain at right side of chest. Lab investigations and intraoperative findings revealed thickened pleura with calcifications, caseating material, adhesions and fluid build-up with a bronchopleural fistula. The patient underwent surgical decortication of right lung and fistula closure, followed by antitubercular therapy. This case emphasizes how critical it is to identify and treat this uncommon issue as soon as possible. It also underscores the need for a multidisciplinary approach in the treatment of such complex cases. Early treatment is key to reducing the risk of death and other complications.